Pyridylpiperazine-based carbodithioates as urease inhibitors: synthesis and biological evaluation - Akash, Muhammad; Rana, Nehal; Aslam, Sana; Ahmad, Matloob; Saif, Muhammad Jawwad; Asghar, Aneeza; Sultan, Sadia; Al-Hussain, Sami A.; Liaqat, Afifa; Zaib, Sumera; Zaki, Magdi E. A. (Frontiers in Chemistry, 2024)
The urease enzyme is recognized as a valuable therapeutic agent for treating the virulent Helicobacter pylori bacterium because of its pivotal role in aiding the colonization and growth of the bacterium within the gastric mucosa. In order to control the harmful consequences of bacterial infections, urease inhibition presents itself as a promising and effective approach. The current research aimed to synthesize pyridylpiperazine-based carbodithioate derivatives 5a–5n and 7a–7n that could serve as potential drug candidates for preventing bacterial infections through urease inhibition. The synthesized carbodithioate derivatives 5a–5n and 7a–7n were explored to assess their ability to inhibit the urease enzyme after their structural explication by gas chromatography–mass spectrometry (GC-MS). In the in vitro evaluation with thiourea as a standard drug, it was observed that all the synthesized compounds exhibited significant inhibitory activity compared to the reference drug. Among the compounds tested, 5j (bearing an o-tolyl moiety) emerged as the most effective inhibitor, displaying strong urease inhibition with an IC50 value of 5.16 ± 2.68 μM. This IC50 value is notably lower than that of thiourea (23 ± 0.03 μM), indicating the significantly most potent potential of inhibition. In molecular docking of 5j within the active site of urease, numerous noteworthy interactions were identified.